Introduction to sociology and anthropology - Palispis, Epitacio S. (Manila, Philippines : Rex Book Store, 2007)
The study of sociology and anthropology has become indispensable to every college student. These two disciplines play a key role in modern intellectual culture and they occupy a central place with the social science. These two disciplines, duly integrated, have become part of the science orientation among beginning college students in the Philippines.
Part One: Foundation in the study of sociology and anthropology -- Part two: The individual in society -- Part three: The human society and communities -- Part Four: Social Institutions -- Part five: The Transformation of society -- References -- Index.
Includes bibliographical references and index.
Keywords: SOCIOLOGY AND SOCIETY